BENTUK KEMITRAAN Djarum Foundation dan Dinas Pendidikan Pemuda dan Olahraga Kabupaten Kudus Dalam Kerangka Corporate Social Responsibility (CSR) - Indra Diki Dewantara; Ahmad Taufiq; Suwanto Adhi (Journal of Politic and Government Studies, 2015)
At first, the concept of CSR is motivated by the company in its motivation charity. Itsimplementation in the form of assistance to the poor communities surrounding the companyin the form of money or the manufacture of means of transport. Then the CSR conceptevolved with emphasis on community empowerment program or better known as communitydevelopment (CD). In the context of CSR, the CD's success is measured by the increase inquality of life in sekitarnya. One of the activities is to involve local communities to workwithin the company. Or by creating a new business in accordance with the capacity of localcommunities. In contrast to the condition of Indonesia, here the corporate socialresponsibility activities began only in recent years. The demands of society and thedevelopment of democracy as well as the swift currents of globalization and the free market,which raises awareness of the industry on the importance of implementing corporate socialresponsibility.As this study aims to determine the model partnership what exists between theMinistry of Youth and Sports Kudus and Djarum Foundation and aid delivery mechanismsDjarum Foundation Corporate Social Responsibility (CSR). In partnership awakened DjarumFoundation was incorporated as a private institution providing assistance to the pattern ofCorporate Social Responsibility (CSR) or Corporate Responsibility Social. Factor ofproduction area which is in the PT Djarum Kudus Regency is the key factor why DjarumFoundation focuses of development in the area of origin in order to compete with otherregions. Where one is to optimize development efforts in the field of vocational education onthe level of cooperation with the Ministry of Youth and2So the results of this partnership can be felt directly by the school as an educationalspace that will provide learning to students in order to become a vocational school graduatesare ready to use. In the course of this partnership, both private public institutions is equallyhave an important and strategic position and serve to complement the needs of each other.Ministry of Youth and Sports Kudus Regency serves as a mediator and facilitator to provideinformation about SMK needed Djarum Foundation, as well as Djarum Foundation serves asthe provider and the owner of the resource which can make a significant contribution to theadvancement of education in vocational shaded by the Ministry of Youth and Sports KudusDistrict.